ARISAN: PRAKTIK AKUNTANSI EMAK-EMAK - Maria Entina Puspita; Elen Krisnianda; Anggun Maulinda Suyatno (ITB AAS Indonesia Surakarta, 2025)
This study aims to detect accounting practices among mothers in the form of arisan according to the perspective of accounts receivable and investment accounting. The objects studied were the arisan actors of mothers in the PKK Mothers group in the RT 6 Mangunsari and RT 5 Kutowinangun Lor areas. The data collection technique used accidental sampling where the research respondents were arisan actors consisting of arisan administrators and arisan participant members who were willing to be studied during the study. The study used primary data in the form of questionnaires for 80 respondents and structured interviews with the arisan managers in the area. This study is a mixed study between a quantitative approach to process the types of accounting information owned by arisan actors and a qualitative approach in the form of interview results with the arisan actors studied. The results of the study show that arisan activities can reflect simple accounts receivable and investment accounting practices. Arisan in accounts receivable accounting is interpreted from the savings activity by its members, while in terms of investment, the motives of members to participate in arisan are to avoid inflation and the management of arisan also looks like an informal financial institution.